Uncooled, broadband terahertz bolometers using SOI MEMS beam resonators with piezoresistive readout - Ya Zhang; Kazuki Ebata; Mirai Iimori; Qian Liu; Zihao Zhao; Ryotaro Takeuchi; Hua Li; Kazusuke Maenaka; Kazuhiko Hirakawa (Microsystems & Nanoengineering)
Abstract Terahertz (THz) detectors using MEMS resonators have attracted great interests owing to their high sensitivity, rapid response, and room-temperature operation capability. For easy integration with CMOS circuits, silicon (Si) based MEMS detectors are highly desirable. Here we report an uncooled THz bolometer using doubly-clamped Si on insulator (SOI) MEMS beam resonator with piezoresistive readout. When external heat is applied to the MEMS beam, the resonance frequency shifts owing to the thermal strain in the beam, demonstrating a thermal responsivity up to 149 W−1. SOI MEMS resonators exhibit a thermal response time of about 88 μs, which is over 3 times faster than that of GaAs MEMS detectors. Furthermore, electrical readout of the MEMS vibrations is achieved by using the piezoresistive effect of Si, offering a low frequency noise density of 2.7 mHz/√Hz, and subsequently a noise equivalent power (NEP) of about 36 pW/√Hz for the current devices. Optical measurement using a FTIR spectrometer shows that SOI MEMS bolometers has a broadband THz response across 1–10 THz range. These results demonstrate that SOI MEMS bolometer features fast response and high sensitivity, while also being compact, broadband, and CMOS-compatible, highlighting its strong potential for advanced THz spectroscopy and imaging applications.